2008
DOI: 10.1111/j.1348-0421.2008.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction detection of bacterial 16S rRNA gene in human blood

Abstract: Bacterial 16S ribosomal RNA genes (rDNA) were detected in blood samples from two healthy individuals by PCR under conditions involving 30 cycles that did not produce any visible products from negative control saline. Even from control samples, PCR involving 35-40 cycles yielded visible bands. Major clones detected in the blood samples, but not in control, were the Aquabacterium subgroup, Stenotrophomonas subgroup, Budvicia subgroup, Serratia subgroup, Bacillus subgroup and Flavobacteria subgroup. No clone was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 28 publications
7
46
0
Order By: Relevance
“…Moreover, we showed that HIV seronegative subjects have detectable 16S ribosomal DNA in the blood, at a level 1 log greater than that of the control samples, for which the signal is likely due to contamination. These results are in agreement with other previous studies [6,7]. In contrast, Jiang et al [1] found no 16S ribosomal DNA in blood from healthy subjects.…”
Section: Plasma Levels Of Bacterial Dna In Hiv Infection: the Limits supporting
confidence: 74%
“…Moreover, we showed that HIV seronegative subjects have detectable 16S ribosomal DNA in the blood, at a level 1 log greater than that of the control samples, for which the signal is likely due to contamination. These results are in agreement with other previous studies [6,7]. In contrast, Jiang et al [1] found no 16S ribosomal DNA in blood from healthy subjects.…”
Section: Plasma Levels Of Bacterial Dna In Hiv Infection: the Limits supporting
confidence: 74%
“…But, in recent decades, presence of bacterial 16S rRNA genes has been reported in the circulation of healthy individuals [24], [25]. Adding to this knowledge are the recent reports on identification of viruses in the circulation of asymptomatic humans [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…Kalfin reported 100% positivity of the blood cultures. Subsequently several other authors questioned the existence of the blood microbiome or DNAemia in healthy individuals, Domingue (1977) [5], (1997) [7], Nikkari et al (2001) [8], Mc Laughlin et al (2002) [9], Moriyama et al (2008) [10], Markova (2015) [11], Damgaard (2015) [12] Dimova et al (2017) [13], Gosiewski et al (2017) [2] and Kowarsky et al (2017) [3]. The authors reported supporting electron microscopy, cultural and molecular data in favour of the existence of the blood microbiota in healthy individuals.…”
Section: Tedeschi Et Al Reported On Incorporation Of Nucleosides In mentioning
confidence: 99%